Utilizing coal remaining resources and post-mining land use planning based on GIS-based optimization method : study case at PT Adaro coal mine in South Kalimantan - Anis, Mohamad; Idrus, Arifudin; Amijaya, Hendra; Subagyo, Subagyo (UIR PRESS, 2017)
Coal mining activities may cause a series of environmental and socio-economic issues in communities around the mining area. Mining can become an obstacle to environmental sustainability and a major hidden danger to the security of the local ecology. Therefore, the coal mining industry should follow some specific principles and factors in achieving sustainable development. These factors include geological conditions, land use, mining technology, environmental sustainability policies and government regulations, socio-economic factors, as well as sustainability optimization for post-mining land use. Resources of the remains of the coal which is defined as the last remaining condition of the resources and reserves of coal when the coal companies have already completed the life of the mine or the expiration of the licensing contract (in accordance with government permission). This research uses approch of knowledge-driven GIS based methods mainly Analytical Hierarchy Process (AHP) and Fuzzy logic for utilizing coal remaining resources and post-mining land use planning. The mining area selected for this study belongs to a PKP2B (Work Agreement for Coal Mining) company named Adaro Indonesia (PT Adaro). The result shows that geologically the existing formation is dominated by Coal Bearing Formation (Warukin Formation) which allows the presence of remains coal resource potential after the lifetime of mine, and the suitability of rubber plantation for the optimization of land use in all mining sites and also in some disposal places in conservation areas and protected forests.